Construction Of Islamic Character Education For Mtss Milbos Students Bogor Indonesia - Zikry Septoyadi; Vita Candrawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
According to researchers, teaching and learning activities at MILBoS are running well, but the school's quality needs to be improved. One key aspect is the need to improve teacher resources to improve learning quality. Teacher supervision and guidance of students are also needed, as are improvements to incomplete facilities, and closer relationships with students. Therefore, this research is urgently needed for innovation and solutions in the world of education. The study,